Learning-by-Doing in the Renewable Energy Equipment Industry or in Renewable Electricity Production: Why Does It Matter to Differentiate? A Case Study of Germany - Katja Schumacher; Michael Kohlhaas (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
In economic models of energy and climate policy, endogenous technological change is generally introduced as the result of either investment in research-and-development or of learningby-doing. In this paper, we analyze alternative ways of modeling learning-by-doing in the renewable energy sector in a top-down CGE model. Conventionally, learning-by-doing effects in the renewable energy sector are allocated to the production of renewable based electricity. We build on the observation that learning-by-doing also takes place in sectors that deliver capital goods to the renewable electricity sector, in particular in the production of machinery and equipment for renewable energy technologies. We therefore implement learning-by-doing alternatively in the renewable energy equipment industry and in renewable electricity production and show why it matters to differentiate between these two approaches. The main differences originate from effects on international trade, since the output of the machinery and equipment sector is intensively traded on international markets unlike renewable electricity.
Keywords: Q43; F10; O30; C68; 330; Learning-by-doing; wind energy; general equilibrium modeling; international trade; Regenerative Energie; Elektrische Energietechnik; Windkraftanlage; Lernprozess; CGE-Modelling; Endogener technischer Fortschritt; Außenwirtschaft; Theorie; Deutschland